Structural and Functional Aspects of Extended-Spectrum AmpC Cephalosporinases - A. Powers, Rachel (Current Drug Targets, 2016)
β-lactam antibiotics have revolutionized modern medicine, but resistance to these drugs is a major public health crisis. Traditionally, class C β-lactamases were referred to as cephalosporinases due to their substrate preference for this particular class of β-lactams. However, the emergence of AmpC enzymes with extended-spectrum activity (extended-spectrum cephalosporinases or ESACs) is particularly worrisome, especially given that most clinical β-lactamase inhibitors are ineffective against these enzymes. This review summarizes structures of several extended spectrum class C β-lactamases and analyzes the structure-function relationship observed among them.
Keywords: β-Lactamase